PEMIKIRAN POLITIK ISLAM INDONESIA OLEH MUHAMMAD NATSIR - Agustina Damanik (Yurisprudentia: Jurnal Hukum Ekonomi, 2018)
History The Indonesian nation records a character named Mohammad Natsir, uniquely. He is prime minister, political figure, movement figure, Islamic figure, as well as educational figure. According to Endang Saefuddin Ansari, M. Natsir is a Dzu Wujuh, has many faces in a good sense. He is a teacher of the nation, an ummah educator and a mujahid da'wah, he is a cultural or cultural thinker, he is a 'pious with all attributes attached to that title, he is a leading politician, he is a prominent statesman, and last but not least he is a respected international figure.M. Natsir argues that Islam is not merely a religion, but a view of life that includes political, economic, social, and cultural matters. The above view is evidenced by various writings in various languages namely Indonesia, English, Arabic or Dutch either about culture, philosophy, education, religion, state administration and so forth.           With extensive political and religious insights, Natsir led the trial of the Islamic Nature Congress in Damascus in 1957, along with Sheikh Maulana Abul A 'la al-Mawdudi (Lahore) and Hasan al-Nadawi (Lucknow). For his services in leading the organization, then in 1980 the Kingdom of Saudi Arabia awarded the "Faisal Award" in honor of its service and devotion to Islam. So widespread is his insight and his views, therefore, in this paper the author limits around M. Natsir's thoughts on political thought, religious thought, and does not forget his biography to answer the question, in this paper simply the author will describe.